TREAT-B Algorithm for Treatment Eligibility Among Chronically Infected Hepatitis B Virus Persons in a Low and a High Endemic Region: A Potential Strategy Towards Virus Elimination by 2030 - Kafeero, Hussein Mukasa; Ndagire, Dorothy; Ocama, Ponsiano; Kato, Charles Drago; Wampande, Eddie; Kajumbula, Henry; Kateete, David Patrick; Walusansa, Abdul; Kudamba, Ali; Ssenku, Jamilu E.; Sendagire, Hakim (Frontiers in Virology, 2022)
Background: Little is known about treatment eligibility in Africa for the hepatitis B virus (TREAT-B) algorithm. We investigated the treatment eligibility among the HBV chronically infected patients in a low and a high endemic region using the TREAT-B algorithm. Methods: We recruited 227 treatment naïve HBV infected hospital attendees from the low and high HBV endemic regions. We assessed the treatment eligibility by testing for HBeAg serostatus and ALT levels. Socio-demographic data were collected with a structured questionnaire. The accessory correlates of treatment eligibility (AST, ALP, ALB, GGT and TBIL) and the socio-demographic factors were analyzed by both univariate and multinomial logistic regression using the SPSS and Medcalc. The analysis was done at 95%CI and a p<0.05 was considered statistically significant. Results: Overall, 56.8% of the participants qualified for treatment at TREAT-B cutoffs of ≥2 with those from the low endemic region (90, 69.8%) having significantly higher treatment eligibility indication than those from the high endemic (p<0.05). Alcohol use and house hold contact with an HBV infected person were independent socio-demographic factors significantly associated with treatment eligibility for both low and high endemic regions (p<0.05). However, birth place was only indicated for treatment eligibility among the high endemic participants (p<0.05). The AST, GGT and total bilirubin were the liver related parameters significantly associated with treatment eligibility among (p<0.05) with GGT and AST being significantly elevated among the eligible low endemic dwellers compared to their high endemic dweller counterparts (p<0.05). Conclusion: Using TREAT-B algorithm can be a plausible alternative to the orthodox methods to specify treatment eligibility with the potential to scale-up interventions targeting HBV management and elimination.